Speaking Pittsburghese - Johnstone, Barbara (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Pittsburgh speech and Pittsburghese -- Yinz are in Stiller Country: Dialect, Place, and Social Meaning in Language -- From Pittsburgh Speech To Pittsburghese -- Perceiving Pittsburghese -- Linking Dialect and Place in Interaction -- Pittsburghese in the Media -- Selling Pittsburghese -- Performing Pittsburghese -- The History of Yinz and the Outlook for Pittsburghese